2015
DOI: 10.5435/jaaos-d-15-00017
|View full text |Cite
|
Sign up to set email alerts
|

Principles of Antibiotic Prophylaxis in Total Joint Arthroplasty

Abstract: Infection is a rare, serious complication following total joint arthroplasty and constitutes a considerable emotional and financial burden for patients, surgeons, and healthcare systems. Prevention of surgical site and periprosthetic joint infections is crucial. This requires knowledge of the microorganisms that commonly cause these infections, including Staphylococcus species. Selection of the appropriate antibiotic regimen to treat infection remains controversial, but cefazolin and cefuroxime are the most co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 63 publications
(86 reference statements)
1
30
1
Order By: Relevance
“…We also included patients with aseptic loosening because some patients might have low‐grade infections in this group. Gram‐positive bacterium is still the most common pathogenic bacteria in PJI, accounting for over 50% of cases, and in our study the proportion of isolated G+ bacteria was 86.9% (60/69); Staphylococcus epidermidis and Staphylococcus aureus were the largest in number.…”
Section: Discussionsupporting
confidence: 45%
See 1 more Smart Citation
“…We also included patients with aseptic loosening because some patients might have low‐grade infections in this group. Gram‐positive bacterium is still the most common pathogenic bacteria in PJI, accounting for over 50% of cases, and in our study the proportion of isolated G+ bacteria was 86.9% (60/69); Staphylococcus epidermidis and Staphylococcus aureus were the largest in number.…”
Section: Discussionsupporting
confidence: 45%
“…Even so, we believe that our study could provide some information on current treatment of PJI. Previous studies have found that decolonization plays an essential role in postoperative infection, and the use of prophylactic antibiotics against the decolonization might decrease the rate of PJI. Further study should focus on finding common decolonizing bacterium in patients undertaking elective orthopaedic surgery in China, and further test the appropriateness of using cefuroxime and clindamycin in prophylaxis in primary TJA.…”
Section: Discussionmentioning
confidence: 99%
“…Prophylactic antibiotics significantly reduce prosthetic joint infection (PJI) rates after hip and knee arthroplasty . Cefazolin antibiotic prophylaxis is the standard of care in New Zealand; however, the rise of antibiotic resistance in recent decades has raised concerns that cephalosporins may no longer provide adequate prophylaxis …”
Section: Introductionmentioning
confidence: 99%
“…1 Cefazolin antibiotic prophylaxis is the standard of care in New Zealand; however, the rise of antibiotic resistance in recent decades has raised concerns that cephalosporins may no longer provide adequate prophylaxis. 2,3 In order for prophylactic antibiotics to be effective, their spectrum of activity must cover the organisms likely to cause intraoperative contamination. 4 In total knee arthroplasty (TKA), antibiotics must be effective against the two most common infective organisms: Staphylococcus aureus and coagulase-negative staphylococci (CoNS).…”
Section: Introductionmentioning
confidence: 99%
“…If preoperative testing indicates that the patient is colonized with methicillin-resistant Staphylococcus aureus (MRSA), studies show an increased risk of surgical-site infection [11]. In these situations, it is recommended either to decolonize the patient before the surgery or to give a one-time dose of vancomycin [12]. In addition to antibiotics, pre-incision intravenous administration of tranexamic acid has been shown in multiple studies to decrease intraoperative blood loss [13,14].…”
Section: Positioning and Drapingmentioning
confidence: 99%